Overview of production in the arts/music area presented in articles published in brazilian journals listed in qualis capes (2017-2020) over the ten years between 2013-2022 (Orfeu, 2024)
This article outlines the state of music research in Brazil, particularly in the manner of publication of articles, highlighting thematic areas and subareas, as well as listing the institutions responsible for publishing them. When it comes to science, written communication is still the main vehicle for disseminating knowledge acquired with research. This traditional form of dispersion of knowledge is basically done through conventional forms, such as scientific papers. This seems to be the starting point for inquiring into the origin and scope of research practices related to music. To carry out this study, we used data collected from the journals listed in the evaluation of the four-year period 2017-2020, available at Sucupira Platform, with the period of analysis being the decade 2013-2022. From this context, all periodicals in the Arts/Music area with electronic access were listed and quantified, with all their articles classified and quantified according to thematic area and subarea. It is believed that, with this, we are contributing to the organization of knowledge, contributing to the perception of the universe of music research and the readings of researchers from different areas of knowledge that are dedicated to the study of music, in its most diverse nuances.
Keywords: scientific publication in music; music topics and subtopics; Art/Music area; Qualis Capes